(untitled) - O'Brien, David M. (New York, NY., 2002)
With the abortion and school desegregation decisions, O'Brien contends, the Supreme Court has ceased to be Hamilton's "least dangerous branch." Increasingly activist, it has in fact become a "storm center" of national politics. Ever mindful of our judicial past, O'Brien likewise finds the Court is markedly more bureaucratic. His lucid text descibes the inner rules and proceduresthe cost of filings, screening procedures, certiorari petitions, the justices' give-and-take negotiations, their tentative votes and maneuverings, the oral arguments, the growing number of dissents and plurality opinions. O'Brien finds the Court rife with heated personal clashes. Rather than above the battle, it is highly sensitive to external pressures, from the President, Congress, public opinion. This is an illuminating, first-rate primer for those seeking to understand the workings of the Court. Milton Cantor, History Dept., Univ. of Massachusetts, Amherst
Keywords: United states,Political questions and judicial power,Judicial processes; Supreme court; United states,United states